Open Access Repositories on Open Educational Resources: Feasibility of Adopting the Japanese Model for Academic Libraries - Chew, Bee Leng; Kamsiah, Mohd Ali; Ch'ng, Eng Hoo (Emerald Group Publishing Limited, 2016)
Purpose Triggered by the advancement of information and communications technology, open access repositories (a variant of digital libraries) is one of the important changes impacting library services. In the context of openness to a wider community to access free resources, Wawasan Open University Library initiated a research project to build open access repositories on open educational resources. Open educational resources (OER) is an area of a multifaceted open movement in education. The purpose of this paper is to show how two web portal repositories on OER materials were developed adopting a Japanese open source software, called WEKO.